Pesticides in the Environment : Biobed Systems as an Innovative Biotechnological Tool to Minimize Pollution - Rodríguez Rodríguez, Carlos E. (2018)
UCR::Vicerrectoría de Investigación::Unidades de Investigación::Ciencias Básicas::Centro en Investigación en Contaminación Ambiental (CICA)